Patterns of specialisation and economic complexity through the lens of universal exhibitions, 1855-1900 - Giacomo Domini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This paper reconstructs Revealed Comparative Advantages (RCA) and Economic Complexity Indices (ECI) for a large number of countries in the second half of the 19th century, by using data from the catalogues of five universal exhibitions held in Paris in 1855, 1867, 1878, 1889, and 1900. This allows overcoming the lack of finely product-disaggregated comparative export data, on which such indices are typically constructed. The analysis of exhibition-based RCAs and ECIs reveals structural change and development processes experienced by countries during those decades, pointing out the relevance of countries' productive structures for long-run growth.
Keywords: F14; F43; N10; O10; O47; O57; 330; patterns of specialisation; revealed comparative advantage; economic complexity; universal exhibitions